Removal of Radioactively Marked Calcium Hydroxide from the Root Canal: Influence of Volume of Irrigation and Activation - Zorzin, José Ignacio; Wiessner, Jessica; Wiessner, Thomas; Lohbauer, Ulrich; Petschelt, Anselm; Ebert, Johannes (Journal of Endodontics, 2016)
The purpose of this study was to evaluate the amount of calcium hydroxide (Ca[OH]2) removed by irrigation with different volumes and activation methods.One hundred thirty extracted straight, single-rooted human teeth were instrumented to size 45/.04. One hundred twenty teeth were filled with radioactively marked Ca(OH)2 and a gutta-percha point; 10 teeth with only gutta-percha served as a negative control. All specimens were stored in saline solution (7 days at 35°C). After storage, teeth were randomly divided into 12 groups (n = 10). The gutta-percha was taken out, and Ca(OH)2 was removed either by irrigation with different volumes (0 mL, 0.5 mL, 1 mL, 2 mL, 4 mL, or 8 mL) or mechanical activation with a 2- or 4-mL volume using a file (Instr) (FlexMaster size 45/.04; VDW, Munich, Germany), a brush (CanalBrush [CB]; Coltène/Whaledent, Langenau, Germany), or passive ultrasonic irrigation (PUI, smooth wire). Irrigation was performed by alternating 40% citric acid and 3% sodium hypochlorite. Residual Ca(OH)2 was measured by scintillation and expressed as a percentage of the original Ca(OH)2.Increasing the irrigation volume led to a significant decrease (P < .05) of residual Ca(OH)2 (0 mL [98.5%], 0.5 mL [21.7%], 1 mL [16.5%], 2 mL [12.9%], 4 mL [8.7%], 8 mL [5.0%], and negative control [0.0%]). Activation led to less residual Ca(OH)2 (2 mL Instr [12.0%], 2 mL CB [11.7%], 2 mL PUI [9.1%], 4 mL Instr [8.5%], 4 mL CB [7.4%], and 4 mL PUI [6.2%]), with significant differences according to the PUI (P < .05).No irrigation procedure was able to remove Ca(OH)2 completely. PUI was the most effective activation method. However, irrigation with an 8-mL volume was the most effective.
EVALuna2:24681